Mengasah Kecerdasan Anak dengan Soal HOTS: Strategi Efektif untuk Pembelajaran di SD - Cindy Marsya Putri; Adrias Adrias; Salmaini Syafitri Syam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Learning based on Higher Order Thinking Skills (HOTS) is an effective strategy for sharpening children's intelligence in elementary schools. HOTS questions are designed to train students' critical, analytical, and creative thinking skills, enabling them to solve problems independently. This article discusses the basic concepts of HOTS questions, strategies for their implementation in learning, and their benefits in improving children's comprehension quality. Several effective strategies in HOTS-based learning include using challenging questions, problem-based learning, reflective discussions, and utilizing technology and interactive media. Additionally, this article identifies the challenges faced in implementing HOTS in elementary schools and solutions that educators can apply. With proper implementation, HOTS questions can help students develop higher-order thinking skills essential for facing future challenges.